2017
DOI: 10.1002/sctm.16-0227
|View full text |Cite|
|
Sign up to set email alerts
|

Allogeneic Bone Marrow-Derived Mesenchymal Stromal Cells Expanded In Vitro for Treatment of Aplastic Anemia: A Multicenter Phase II Trial

Abstract: We conducted a phase II, noncomparative, multicenter study to assess the efficacy and safety of allogeneic bone marrow‐derived mesenchymal stromal cells (BM‐MSCs) expanded in vitro for patients with aplastic anemia (AA) refractory to immunosuppressive therapy. Seventy‐four patients from seven centers received allogeneic BM‐MSCs at a dose of 1–2 × 106 cells/kg per week for 4 weeks. Responses were assessed at 0.5, 1, 2, 3, 6, 9, and 12 months after the first cells infusion. Patients with response at 1 month cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 43 publications
(72 reference statements)
2
20
1
Order By: Relevance
“…Allogeneic transplant of MSCs can be a potential supplementary alternative to treat refractory SAA, since these cells are hypoimmunogenic, thus displaying low expression levels of human leukocyte antigen (HLA) class I, no expression of HLA class II [ 18 ]. Potentially, these cells may also be an addition to IS therapies because they possess broad immunomodulatory properties, secreting several biological molecules that influence both adaptive and innate immune responses [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Allogeneic transplant of MSCs can be a potential supplementary alternative to treat refractory SAA, since these cells are hypoimmunogenic, thus displaying low expression levels of human leukocyte antigen (HLA) class I, no expression of HLA class II [ 18 ]. Potentially, these cells may also be an addition to IS therapies because they possess broad immunomodulatory properties, secreting several biological molecules that influence both adaptive and innate immune responses [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…In view of the association of SAA with immune‐mediated HSC destruction and BM microenvironmental insufficiency, MSCs offer new approaches for the treatment of this disorder. MSC infusions were applied as monotherapy in patients with refractory SAA and produced modest responses with complete or partial response rates ranging from 22% to 33% . By contrast, additive MSC infusions with HSCs were promising with better and faster engraftment in most patients receiving HSC transplantation .…”
Section: Discussionmentioning
confidence: 99%
“…The study development by Pang et al showed, six of 18 patients (33.3%) achieved a complete response or a partial response to MSCs treatment [107]. In six patients, two achieved a complete response including recovery of three hematopoietic cell lines after MSCs therapy.…”
Section: Clinical Studies With Msc For Treat Aamentioning
confidence: 99%
“…One patient with RAEB-II died of disease progression, two patients died of intracranial hemorrhages, and six patients died of serious infection [107]. In other two studies were reported adverse events such as, fever, hypoxemia, mild dyspnea and diarrhea during MSCs administration or some hours after MSCs injection, this phenomenon occurs in 2 of 16 patients [107] and 7 of the 18 patients [108]. None major adverse effects were reported in all studies during months of follow-up of each respective study.…”
Section: Clinical Studies With Msc For Treat Aamentioning
confidence: 99%